Down-regulation of an Auxin Response Factor in the tomato induces modification of fine pectin structure and tissue architecture - Guillon, Fabienne (Journal of experimental botany, 2008)
It has previously been shown that down-regulation of an auxin response factor gene (DR12) results in pleiotropic phenotypes including enhanced fruit firmness in antisense transgenic tomato (AS-DR12). To uncover the nature of the ripening-associated modifications affecting fruit texture, comparative analyses were performed of pectin composition and structure in cell wall pericarp tissue of wild-type and AS-DR12 fruit at mature green (MG) and red-ripe (RR) stages. Throughout ripening, pectin showed a decrease in methyl esterification and in the content of galactan side chains in both genotypes. At mature green stage, pectin content in methyl ester groups was slightly higher in AS-DR12 fruit than in wild type, but this ratio was reversed at the red-ripe stage. The amount of water- and oxalate-soluble pectins increased at the red-ripe stage in the wild type, but decreased in AS-DR12. The distribution of methyl ester groups on the homogalaturonan backbone differed between the two genotypes. There was no evidence of more calcium cross-linked homogalacturan involved in cell-to-cell adhesion in AS-DR12 compared with wild-type fruit. Furthermore, the outer pericarp contains higher proportion of small cells in AS-DR12 fruit than in wild type and higher occurrence of (1-->5) alpha-L-arabinan epitope at the RR stage. It is concluded that the increased firmness of transgenic fruit does not result from a major impairment of ripening-related pectin metabolism, but rather involves differences in pectin fine structure associated with changes in tissue architecture